2021
DOI: 10.1186/s40538-021-00214-x
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the research of Angelica sinensis (Oliv.) Diels polysaccharides: extraction, purification, structure and bioactivities

Abstract: The root of Angelica sinensis (Oliv.) Diels, a well-known Chinese herbal medicine, has been used historically as hematopoietic and anti-inflammatory agents for thousands of years. Recent phytochemistry and pharmacological studies have proved that polysaccharides are one of the major active ingredients in A. sinensis. It has been demonstrated that ASPs (A. sinensis polysaccharides) had various important biological activities, such as hematopoietic, hepatoprotective, hypoglycemic, anti-inflammatory, antitumor, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 64 publications
(92 reference statements)
0
61
0
Order By: Relevance
“…Studies have shown the major benefits of the integrated optical circuits (IOCs) over electronic integrated circuits (EICs) [1][2][3][4][5][6][7][8][9][10][11][12]. In fact, IOCs enjoy lower loss rate, a much greater propagation speed, lower error rate of data transmission, as well as very high security in comparison with the electrons in EICs [12][13][14][15][16][17][18][19][20][21][22][23][24]. On the one hand, they have contributed importantly to the design of all-optical circuits because of their specific features, one of which is that their photonic bandgap (PBG) that prevents lights of certain wavelengths from propagating in one, two, or any number of polarization directions within the PhC structure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the major benefits of the integrated optical circuits (IOCs) over electronic integrated circuits (EICs) [1][2][3][4][5][6][7][8][9][10][11][12]. In fact, IOCs enjoy lower loss rate, a much greater propagation speed, lower error rate of data transmission, as well as very high security in comparison with the electrons in EICs [12][13][14][15][16][17][18][19][20][21][22][23][24]. On the one hand, they have contributed importantly to the design of all-optical circuits because of their specific features, one of which is that their photonic bandgap (PBG) that prevents lights of certain wavelengths from propagating in one, two, or any number of polarization directions within the PhC structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that UPRmt in the mitochondrial matrix mainly relies on activating the mitochondrial chaperone HSP60 and the protease CLPP [32,[34][35][36]. In contrast, UPRmt in the mitochondrial intercellular space (IMS) is associated with the expression of membrane interstitial protein HTRA2 [37][38][39]. In addition, the antioxidant effect of the UPRmt sirtuin axis is also crucial for the stability of mitochondrial reconstruction protein [35].…”
Section: Introductionmentioning
confidence: 99%
“…More refined purification methods include ion-exchange chromatography, which is a widely used purification technology, using gradient salt elution to separate neutral and acidic polysaccharides. Gel filtration column chromatography is commonly adopted for separating polysaccharides with different molecular weights (Ji et al, 2020(Ji et al, , 2021Hou et al, 2021). Three polysaccharide fractions with different molecular weight isolated from the same species exhibited totally different antioxidant activity in vitro (Meng et al, 2015;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%